Total Synthesis of Natural Products with Antimicrobial Activity - Giltrap, Andrew (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This thesis focuses on the development of efficient and scalable total syntheses of natural products that can be used as preferred scaffolds for anti-infective drug discovery. It describes the total synthesis of two classes of antimicrobial non-ribosomal peptides (NRPs) - teixobactin and the skyllamycins - with subsequent biological evaluation. The first part describes the first total synthesis of teixobactin by means of a solid-phase peptide synthesis-macrolactamisation approach, yielding a synthetic natural product that can combat a number of clinically relevant Gram-positive bacterial pathogens. The second part describes the first total synthesis of skyllamycins A-C, a family of structurally complex cyclic NRPs, which inhibit the growth of the Pseudomonas aeruginosa biofilms that are responsible for significant mortality among cystic fibrosis patients.